A review of digger wasp genus Harpactus Shuckard, 1837 (Hymenoptera: Crabronidae) of the Indian subcontinent, with description of a new species and rediscovery of Harpactus impudens (Nurse, 1903) - Binoy, C.; Kumar, P. Girish; Monks, Joseph; Sheikh, Altaf Hussain (Zootaxa, 2022)
The digger wasp genus Harpactus Shuckard (Crabronidae: Bembicinae) of the Indian subcontinent is reviewed, resulting in the discovery of a new species H. pulawskii Binoy & Girish Kumar and the rediscovery of H. impudens (Nurse) after more than a century since its description. All species are illustrated, including the holotypes of H. ornatus F. Smith and H. vividus (Turner) whose illustrations were provided by the Natural History Museum, London (NHMUK). Brief diagnoses and a key to species are also given.